Antimicrobial Activity of Combination Bacteriocin and Asam Sunti Extract (Averrhoa bilimbi L. fermented) Against Multidrug Resistant Escherichia coli in Lettuces (Lactuca sativa) - Kimbal, Angie Via Resty; Jatmiko, Yoga Dwi; Ardyati, Tri (The Journal of Experimental Life Science, 2021)
The ready-to-eat vegetables are often associated with the presence of multidrug-resistant (MDR) bacteria. This study aimed to evaluate the potency of bacteriocin, Asam Sunti extract, and their combination against MDR E. coli in lettuce. Their antimicrobial activity was assessed using the disk diffusion method and bacterial enumeration after direct application in pre-inoculated lettuce with MDR E. coli. The bacteriocin was produced by Lactobacillus plantarum BP102 at optimum production time or during the stationary phase at 18 h. These bacteriocins were able to inhibit five MDR E. coli isolates, while Asam Sunti extract and the combination of bacteriocin and Asam Sunti extract were only able to inhibit three MDR E. coli (LL1.2, LL3.11, and LL3.12) and (LL1.2, LL1.3, and LL3.11), respectively. In direct application to pre-inoculated fresh lettuce, higher inhibition of MDR E. coli was observed after applying the combination of bacteriocin and Asam Sunti extract with a ratio of 1:1 and 1:2, compared to bacteriocin alone. However, the inhibitory activity of this combination treatment was not significantly different (p>0.05) with the Asam Sunti extract alone. The highest rate of decrease in total bacteria in lettuces was 97% occurred in isolate LL1.2 with bacteriocin treatment alone, and isolate LL3.11 with combination treatment of bacteriocin and Asam Sunti extract (1:2). While on MCA media, the best reduction rate of 94% occurred in isolate LL1.2 with treatment using bacteriocin only, Asam Sunti extract only, and their combination (1:2). The inhibition of MDR E. coli in fresh lettuces by bacteriocin, Asam Sunti extract, and their combination was strain-dependent which was indicated by various inhibition results in all treatments.Key words: Asam Sunti extract, Bacteriocin, multidrug resistant.